Phase-imprinting of Bose-Einstein condensates with Rydberg impurities - Mukherjee, Rick; Ates, Cenap; Li, Weibin; Wüster, Sebastian (American Physical Society, 2015)
We show how the phase profile of Bose-Einstein condensates can be engineered through its in- teraction with localized Rydberg excitations. The interaction is made controllable and long-range by off-resonantly coupling the condensate to another Rydberg state with laser light. Our technique allows the mapping of entanglement generated in systems of few strongly interacting Rydberg atoms onto much larger atom clouds in hybrid setups. As an example we discuss the creation of a spatial mesoscopic superposition state from a bright soliton. Additionally, the phase imprinted onto the condensate using the Rydberg excitations is a diagnostic tool for the latter. For example a condensate time-of-flight image would permit reconstructing the pattern of an embedded Rydberg crystal.